Penguatan Bahasa Asing Melalui Program Kampung Bahasa Di Kebumen (Studi Manajemen dan Sistem Pembelajaran) - Ali Muhdi; Muhamamd Syadid Daelami (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
The purpose of this research is to find out the comparative management of the Kebumen Arabic Villages (KAK) and Kebumen English Villages (KIK) programs and the foreign language learning system in these programs. The research method used by researchers is a qualitative descriptive method. This type of research includes field research. This research resulted in the first conclusion that the development of a management system for foreign language educational institutions carried out by the Kebumen Arab Village and the Kebumen English Village had used management steps including planning, organizing, actuating, controlling, and evaluating. However, in the planning aspect, it seems that KIK is more organized administratively than KAK. In the organizing aspect it can be said that it is the same in the two language villages, namely that officers or persons in charge of each field of activity have assigned tasks in an orderly manner. In the actuating aspect of KIK there are more outdoor activities while in KAK there are more learning activities in the classroom. In the controlling aspect, KIK involves a lot of roles from elements of the education office and the Ministry of Religion compared to KAK, which is more controlled by a teaching team from the local environment (Al-Istiqomah Islamic Boarding School). While the evaluating aspect is almost the same in both KIK and KAK, namely by holding evaluation activities through joint coordination meetings between district management elements and local teaching teams. Second, the development of the language learning system in KAK and KIK is that the methods used in learning in the English village are almost the same as in the Arab village because both methods are inspired by the existing foreign language teaching models.